The effect of Phosphorus on the growth, plant mineral content and essential oil composition of Buchu (Agathosma betulina) - De Villiers, Chris Johan (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MScAgric (Agronomy)--University of Stellenbosch, 2007.